Alternative Environment Activities in Physical Education: A Research-Informed Rationale and Practical Suggestions for Teacher Practice. Issue 1 (2nd January 2022) - Hall, Nathan; Robinson, Daniel B.; Bradford, Brent; Costa, José da
Abstract : This article discusses the importance of PE teacher embracement of AEAs, provides several specific practical examples for PE teachers looking to enhance AEA inclusion in their PE programs, and concludes with practical strategies to help overcome common PE teacher-cited barriers related to embracing AEAs.